PENGARUH INTENSITAS CAHAYA TERHADAP DEGRADASI WARNA AGARAGAR YANG DIWARNAI SARI UMBI BIT MERAH (Beta vulgaris L. var. rubra L.) - Lydia Ninan Lestario; Noviana Gunawan; Yohanes Martono (Agric, 2013)
The aims of this research were to determine the concentration of beetroot juice in jelly which panelists like best; to determine the color degradation rate constant in jelly colored with beetroot juice caused by sunlight and fluorescent light; and color degradation rate constant of jelly colored with synthetic colorant.The organoleptic test used 2,5 percent; 5 percent; 7,5 percent; 10 percent; and 12,5 percent beetroot juice and permitted synthetic colorant for food. The light intensity to test the beetroot color stability in jelly were 879,06 lux, 1.688,54 lux, 2.342,2 lux and 6.752,2 lux.The results showed that the concentration of beetroot juice which panelists like best was 5 percent.; The color degradation rate constant of jelly colored by 5 percent beetroot juice on intensity 879,06 lux was 0,0468 hour-1; 1.688,54 lux was 0,0565 hour-1; 2.342,2 lux was 0,0653 hour-1;6.752,2 lux was 0,0887 hour-1. The higher the light intensity, the higher the degradation constant rate.